Investigation of calcium sulfate dihydrate crystallization in the presence of glutamic acid in MSMPR crystallizer - (:unkn) unknown (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2017)
In this study, calcium sulfate dihydrate crystallization was performed in a laboratory scale mixed-suspension mixed-product removal (MSMPR) crystallizer at 2.5 pH, 65 degrees C and tau = 0.5 hour in the absence and the presence of glutamic acid. The experiments were carried out at different glutamic acid concentrations as 250 ppm, 1000 ppm and 2500 ppm by the reaction of calcium carbonate solution (20% w/w) with sulfuric acid (20% w/w) solution. The crystal size distributions, filtration rates and zeta potentials of the crystals obtained were measured and the crystals were analyzed by XRD, TGA-FTIR-MS and SEM. It was determined that the width/length ratio of the calcium sulfate dihydrate crystals changed, the filtration rate decreased and the average particle size decreased from 73 mu m to 54 mu m depending on increasing glutamic acid concentration. The calcium sulfate dihydrate crystallization kinetic was examined on the basis of McCabe's Delta L law and the crystal growth was found to be dependent on crystal size. Furthermore, the growth rate of crystals was determined using ASL, C-R, MJ2, and MJ3 model. By comparison of the results of mean square error analysis, it was found that the MJ3 model was the best model to characterize the system. The effect of glutamic acid on the crystal habit was also shown by SEM analysis.
Keywords: Calcium sulfate dihydrate; glutamic acid; crystallization kinetic models; characterization; KINETICS; IMPURITIES; NUCLEATION